Early-stage phenotyping of sweet potato virus disease caused by sweet potato chlorotic stunt virus and sweet potato virus C to support breeding - David, M.; Kante, M.; Fuentes, S.; Eyzaguirre, R.; Diaz, F.; Boeck, B. de; Mwanga, Robert O.M.; Kreuze, Jan F.; Grüneberg, W.J. (Scientific Societies, 2023)
Sweet potato virus disease (SPVD) is a global constraint to sweetpotato (Ipomoea batatas) production, especially under intensive cultivation in the humid tropics such as East Africa. The objectives of this study were to develop a precision SPVD phenotyping protocol, to find new SPVD-resistant genotypes, and to standardize the first stages of screening for SPVD resistance. The first part of the protocol was based on ELISA results for sweet potato chlorotic stunt virus (SPCSV) and sweet potato virus C (SPVC) with adjustments to a negative control (uninfected clone 'Tanzania') and was performed on a pre-breeding population (VZ08) comprising 455 clones and 27 check clones graft-inoculated under screenhouse conditions. The second part included field studies with 52 selected clones for SPCSV resistance from VZ08 and eight checks. In screenhouse conditions, the resistant and susceptible check clones performed as expected, 63 clones from VZ08 exhibited lower relative absorbance values for SPCSV and SPVC than inoculated check Tanzania. Field experiments confirmed SPVD resistance of several clones selected by relative absorbance values (nine resistant clones in two locations, i.e. 17.3% of the screenhouse selection), supporting the reliability of our method for SPVD-resistance selection. Two clones were promising, exhibiting high storage root yields of 28.7-34.9 t ha-1 and SPVD resistance, based on the proposed selection procedure. This modified serological analysis for SPVD-resistance phenotyping might lead to more efficient development of resistant varieties by reducing costs and time at early stages, and provide solid data for marker assisted selection with a quantitative tool for classifying resistance.